Wear-resistant coating with adjustable hardness and high bonding strength as well as preparation method and application of wear-resistant coating

Through the design of the vacuum welding process and gradient metal cloth design, the problem of low connection intensity and WC burn is easy to burn in the existing WC coating preparation method, and realized the hardness regulating and binding strength -resistant coating. The demand for high -hardness and abrasion resistance for industrial production.

CN119352007AActive Publication Date: 2025-01-24SHANGHAI SECOND POLYTECHNIC UNIVERSITY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411920900.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing WC coating preparation methods have problems such as low connection strength, inability to guarantee the coating thickness, low powder utilization rate, and easy burn-out of WC, which is difficult to meet the needs of industrial production for high hardness and high wear resistance.

Method used

Machining the WC coating material through the vacuum welding process, the design of the gradient metal cloth is adopted, and the quality ratio of WC and Nicrbsi is adjusted to prepare the hardness adjustment and high -strength wear -resistant coating.

Benefits of technology

The hardness regulatory and binding strength of the coating is achieved, the coating surface is flat, the molding effect is good, the molding effect is high, high -hardness and high wear resistance, and at the same time, the defects in existing technologies are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352007A_ABST
    Figure CN119352007A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant coating with adjustable hardness and high bonding strength as well as a preparation method and application thereof, and belongs to the technical field of surface engineering. The wear-resistant coating disclosed by the invention is obtained by overlapping and rolling metal cloth I and metal cloth II into gradient metal cloth, placing the gradient metal cloth on the surface of a 45 steel pipe and adopting a vacuum brazing process; the metal cloth I and the metal cloth II are prepared through powder mixing, ball milling and rolling processes, and raw materials comprise WC powder, NiCrBSi powder and an organic additive; wherein by adjusting the weight ratio of the WC powder to the NiCrBSi powder in the metal cloth, the hardness of the wear-resistant coating is adjusted and controlled, and the bonding strength of the wear-resistant coating and the base material is improved. After the surface of 45 steel is coated with the gradient metal cloth, a wear-resistant coating obtained after vacuum brazing is uniform and flat, good in forming, free of cracks and controllable in hardness, and the bonding strength of the coating and a 45 steel pipe base body is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface engineering, and in particular relates to a wear-resistant coating with adjustable hardness and high bonding strength, and a preparation method and application thereof. Background Art

[0002] WC has good wettability, high melting point and high hardness, and is often used as a reinforcing phase in metal coatings. WC-reinforced NiCrBSi alloy coatings have the excellent properties of both, and have high hardness and high wear resistance while ensuring the bonding strength between the coating and the base material. Thermal spraying and surfacing are commonly used processes for introducing WC reinforcing phases into metal coatings in industrial production, but due to the improvement of the working environment and surface performance requirements of the workpiece, these wear-resistant treatment methods have gradually failed to meet the needs of actual production. For example: the connection strength between the thermal spray coating and the substrate is not high, the coating thickness cannot be guaranteed, and the powder utilization rate is low; the surfacing process is heated unevenly, the temperature gradient is large, WC is easy to burn, and the prepared WC coating with a high mass percentage content has cracks. Therefore, the existing WC coating preparation method still needs to be improved.

[0003] Vacuum brazing is an advanced welding method with no pollution, no light, no heat, and no smoke. While ensuring the utilization rate of WC particles, the electronic system accurately controls the metallurgical bonding between the matrix phase and the metal matrix. The matrix phase wraps the reinforcement phase, thereby preparing a wear-resistant coating with high hardness and wear resistance.

[0004] Based on this, how to use vacuum brazing technology to process WC coating materials and prepare a coating composite material with high hardness and high bonding strength has become a problem that needs to be solved at present. Summary of the invention

[0005] The first purpose of the present invention is to provide a wear-resistant coating with adjustable hardness and high bonding strength, the coating has good forming effect and a smooth coating surface.

[0006] The second object of the present invention is to provide a method for preparing a wear-resistant coating, which can obtain a wear-resistant coating with a high WC percentage content by changing the mass ratio of WC and NiCrBSi.

[0007] The third purpose of the present invention is to propose an application of a wear-resistant coating with adjustable hardness and high bonding strength. The gradient metal cloth prepared by the above method is coated on the surface of the metal substrate, and the wear-resistant coating obtained by vacuum brazing has a high bonding strength with the substrate.

[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0009] A wear-resistant coating with adjustable hardness and high bonding strength, wherein the wear-resistant coating is obtained by stacking and rolling a metal cloth I and a metal cloth II into a gradient metal cloth, placing the metal cloth on the surface of a 45 steel pipe and adopting a vacuum brazing process; wherein the metal cloth I and the metal cloth II are both prepared from WC powder, NiCrBSi powder and an organic additive by powder mixing, ball milling and rolling processes; wherein the hardness of the wear-resistant coating is regulated by adjusting the ratio of WC powder to NiCrBSi powder in the metal cloth, thereby improving the bonding strength between the wear-resistant coating and the substrate.

[0010] Furthermore, in terms of mass percentage, in the metal cloth I, WC powder: NiCrBSi powder = 10%: 90%~50%: 50%; in the metal cloth II, WC powder: NiCrBSi powder = 90%: 10%~50%: 50%; the mass ratio of the mixed powder composed of WC powder and NiCrBSi powder to the organic additive in metal cloth I and metal cloth II is 30:1.

[0011] Furthermore, in terms of mass percentage, in the metal cloth I, WC powder: NiCrBSi powder = 10%: 90%; in the metal cloth II, WC powder: NiCrBSi powder = 90%: 10%.

[0012] Furthermore, the organic additive consists of 2.4wt.% dispersant, 9.6wt.% binder, 4wt.% plasticizer and 84wt.% solvent; the dispersant is Hypermer KD-1; the binder is PVB; the plasticizer is selected from PEG and glycerol; the solvent is selected from anhydrous ethanol and butanone.

[0013] Furthermore, any of the above-mentioned methods for preparing the gradient metal cloth comprises the following steps:

[0014] (1) Weighing WC powder and NiCrBSi alloy powder according to mass percentage, mixing them to obtain a mixed powder;

[0015] (2) adding the mixed powder obtained in step (1) and the organic additive into a ball mill at a mass ratio of 30:1, and obtaining a uniform mixture after ball milling;

[0016] (3) placing the uniform mixture obtained in step (2) into a mold, and after demolding, obtaining a rectangular block with a thickness of 4 to 6 mm; rolling the rectangular block, preliminarily adjusting the distance between the rollers to 4 to 5 mm, the rolling temperature to 30 to 40° C., the rolling rate to 0.2 m / min, the rectangular block passes through the rollers, is folded, and rotated 90°, and this step is repeated 4 to 5 times to obtain a rectangular block with a thickness of 4 to 5 mm;

[0017] (4) The distance between the rollers is adjusted to 1.2 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly, and this step is repeated 4 to 5 times to obtain a metal cloth I with a thickness of 1.2 mm; the distance between the rollers is adjusted to 0.8 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly, and this step is repeated 4 to 5 times to obtain a metal cloth II with a thickness of 0.8 mm;

[0018] (5) The metal cloth I and the metal cloth II obtained in step (4) are superimposed, the roller spacing is adjusted to 1.5 mm, and a gradient metal cloth is formed by rolling.

[0019] Furthermore, in the step (2), the ball-to-material ratio of the ball mill is 5:1, the rotation speed is 230 rpm, and the time is 1 hour; the ball milling method is forward rotation-reverse rotation alternating operation.

[0020] Furthermore, in the step (5), the metal cloth is superimposed and rolled in such a manner that the metal cloth II is on the upper side as a layer away from the substrate, and the metal cloth I is on the lower side as a layer close to the substrate.

[0021] Furthermore, the gradient metal cloth is used in metal surface processing, and the method is: the gradient metal cloth is coated on the surface of the metal substrate, and a wear-resistant coating is prepared by a vacuum brazing method, and the steps are as follows:

[0022] (1) Apply silicone epoxy resin AB glue evenly on the surface of DN50×10×50 45 steel pipe; cut the wear-resistant coating into 160×50×1.5mm metal cloth, wrap the cut gradient metal cloth on the surface of 45 steel pipe, then cover the surface of the metal cloth with high-temperature resistant ceramic fiber mat, and wrap and fasten it with steel wire mesh;

[0023] (2) Place the prepared sample upright in a vacuum brazing furnace, heat it to 350°C at a heating rate of 10°C / min, keep it warm for 30 minutes, then continue to heat it to 1050°C, keep it warm for 20 minutes, and then cool it to 700°C at a rate of 5°C / min. Cool it to room temperature with the furnace, take out the sample, and the surface processing of the 45 steel pipe is completed.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1) The gradient metal cloth prepared by the present invention has uniform and dense composition, and the final thickness of the gradient metal cloth can be controlled by adjusting the distance between the rollers of the roller press.

[0026] 2) The gradient metal cloth prepared by the present invention has a certain toughness, and after cutting, it can be used to manufacture coatings on the surfaces of workpieces in the shapes of planes, vertical surfaces, curved surfaces, tortuous surfaces, etc.

[0027] 3) The hardness and wear resistance of the obtained coating can be changed by changing the mass ratio of WC and NiCrBSi in the gradient metal cloth prepared by the present invention.

[0028] 4) After vacuum brazing of the gradient metal cloth, the obtained coating has good forming effect and a smooth surface; the NiCrBSi content is high near the substrate, and the coating has high bonding strength with the substrate; near the surface, the WC content is high, and a crack-free, highly wear-resistant coating with a surface WC content greater than 90% is obtained. The surface has high hardness and high wear resistance.

[0029] 5) Vacuum brazing accurately controls the welding temperature and vacuum degree, and the temperature uniformity in the furnace is good. There is no light, no heat, no smoke, and no pollution during the vacuum brazing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The actual pictures of the coatings obtained by vacuum brazing of metal cloths with the same metal powder content and different organic additive contents, wherein from left to right they correspond to Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 6, Comparative Example 4 and Comparative Example 5 respectively;

[0031] Figure 2 This is the microstructure diagram of the coating in Example 6;

[0032] Figure 3 This is the microstructure diagram of the coating in Example 7;

[0033] Figure 4 This is the microstructure diagram of the coating in Example 8;

[0034] Figure 5 This is the microstructure diagram of the coating in Example 9;

[0035] Figure 6 This is the microstructure diagram of the coating in Example 10. DETAILED DESCRIPTION

[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0037] Unless otherwise specified, the raw materials used in the following examples are commercially available products.

[0038] The formula of the organic additives used in the following embodiments of the present invention is shown in the following table:

[0039]

[0040] Note: Anhydrous ethanol and butanone are miscible. Anhydrous ethanol is a polar molecule containing hydrogen bonds, while butanone is a molecule containing a carbonyl group (C=O) and has polar properties. They both have polar molecular structures, so they can be dissolved through intermolecular interactions (such as hydrogen bonds and dipole-dipole interactions). Both ethanol and butanone are relatively polar organic solvents, and their solubility in each other is relatively high. In particular, ethanol has a strong polarity and can interact with the polar part of the butanone molecule.

[0041] Polyvinyl butyral (PVB) is dissolved in anhydrous ethanol, and Hypermer KD-1 is dissolved in butanone solvent. Anhydrous ethanol, butanone and dispersant (HYKD-1) are first mixed evenly, and then a binder (PVB) and a plasticizer (PEG and propylene glycol) are added and mixed to prepare an organic additive.

[0042] The grain sizes of the WC powder particles used in the present invention are composed of three specifications of 80-100 meshes, 180-200 meshes and 250-300 meshes, and the ratio thereof is 1:2:2.

[0043] The grain size of the NiCrBSi powder used in the present invention is 200 meshes.

[0044] The rolling process adopted in the present invention is carried out at room temperature; the vacuum brazing equipment adopted is a VB-8812MD vacuum brazing furnace.

[0045] Hardness test method: Cut out a 10mm×10mm×10mm coating sample by wire cutting, grind the upper and lower surfaces parallel, and polish the tested plane after water grinding. Use HRS-150 Rockwell hardness tester to measure the surface hardness of the wear-resistant coating, the indenter is diamond, the load is 150Kg, and the holding time is 10s. According to the standard, the distance between the test point and the edge of the sample is not less than 2mm, and the distance between points is set to 2mm. Each data is measured 6 times and the average value is taken.

[0046] Test method for bonding strength: Use CMT5205 electronic universal testing machine and homemade shear fixture to peel off the coating from the substrate. Take 3 shear specimens for each coating sample. The size of the specimen is 5mm×5mm×10mm. The displacement rate of the indenter loading is 0.3mm / min. The average value of the measurement results is taken as the bonding strength of the coating interface.

[0047] Example 1

[0048] A gradient metal cloth comprises metal cloth I and metal cloth II; wherein metal cloth I comprises mixed powder (by mass percentage, 10% WC powder, 90% NiCrBSi powder) and organic additives; metal cloth II comprises mixed powder (by mass percentage, 90% WC powder, 10% NiCrBSi powder) and organic additives. In metal cloth I and metal cloth II, the mass ratio of mixed powder to organic additives is 30:1.

[0049] The method for preparing the metal coating comprises the following steps:

[0050] (1) Weighing WC powder and NiCrBSi alloy powder according to mass percentage, mixing them to obtain a mixed powder;

[0051] (2) adding the mixed powder obtained in step (1) and the organic additive in a mass ratio of 30:1 into a ball mill with a ball-to-material ratio of 5:1 and a rotation speed of 230 rpm, and running the mill in a forward-reverse alternating manner for 1 hour to obtain a uniform mixture;

[0052] (3) placing the uniform mixture obtained in step (2) in a rectangular mold frame for compaction, and obtaining a rectangular block with a thickness of 4 to 6 mm after demolding; placing the rectangular block on an automatic rolling device for rolling, first preliminarily adjusting the distance between the rollers to 4 to 5 mm, the rolling temperature to 30 to 40° C., and the rolling rate to 0.2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and repeatedly rolled, and this step is repeated 4 to 5 times to obtain a rectangular block with a thickness of 4 to 5 mm;

[0053] (4) The distance between the rollers is adjusted to 1.2 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth I with a thickness of 1.2 mm; the distance between the rollers is adjusted to 0.8 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth II with a thickness of 0.8 mm.

[0054] (5) The metal cloth I and the metal cloth II obtained in step (4) are superimposed, the roller spacing is adjusted to 1.5 mm, and a gradient metal cloth is formed by rolling.

[0055] Example 2

[0056] A gradient metal cloth comprises metal cloth I and metal cloth II; wherein metal cloth I comprises mixed powder (by mass percentage, 20% WC powder, 80% NiCrBSi powder) and organic additives; metal cloth II comprises mixed powder (by mass percentage, 80% WC powder, 20% NiCrBSi powder) and organic additives. In metal cloth I and metal cloth II, the mass ratio of mixed powder to organic additives is 30:1.

[0057] The method for preparing the metal coating comprises the following steps:

[0058] (1) Weighing WC powder and NiCrBSi alloy powder according to mass percentage, mixing them to obtain a mixed powder;

[0059] (2) adding the mixed powder obtained in step (1) and the organic additive in a mass ratio of 30:1 into a ball mill with a ball-to-material ratio of 5:1 and a rotation speed of 230 rpm, and running the mill in a forward-reverse alternating manner for 1 hour to obtain a uniform mixture;

[0060] (3) placing the uniform mixture obtained in step (2) in a rectangular mold frame for compaction, and obtaining a rectangular block with a thickness of 4 to 6 mm after demolding; placing the rectangular block on an automatic rolling device for rolling, first preliminarily adjusting the distance between the rollers to 4 to 5 mm, the rolling temperature to 30 to 40° C., and the rolling rate to 0.2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and repeatedly rolled, and this step is repeated 4 to 5 times to obtain a rectangular block with a thickness of 4 to 5 mm;

[0061] (4) The distance between the rollers is adjusted to 1.2 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth I with a thickness of 1.2 mm; the distance between the rollers is adjusted to 0.8 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth II with a thickness of 0.8 mm.

[0062] (5) The metal cloth I and the metal cloth II obtained in step (4) are superimposed, the roller spacing is adjusted to 1.5 mm, and a gradient metal cloth is formed by rolling.

[0063] Example 3

[0064] A gradient metal cloth comprises metal cloth I and metal cloth II; wherein metal cloth I comprises mixed powder (by mass percentage, 30% WC powder, 70% NiCrBSi powder) and organic additives; metal cloth II comprises mixed powder (by mass percentage, 70% WC powder, 30% NiCrBSi powder) and organic additives. In both metal cloth I and metal cloth II, the mass ratio of the mixed powder to the organic additive is 30:1.

[0065] The method for preparing the metal coating comprises the following steps:

[0066] (1) Weighing WC powder and NiCrBSi alloy powder according to mass percentage, mixing them to obtain a mixed powder;

[0067] (2) adding the mixed powder obtained in step (1) and the organic additive in a mass ratio of 30:1 into a ball mill with a ball-to-material ratio of 5:1 and a rotation speed of 230 rpm, and running the mill in a forward-reverse alternating manner for 1 hour to obtain a uniform mixture;

[0068] (3) placing the uniform mixture obtained in step (2) in a rectangular mold frame for compaction, and obtaining a rectangular block with a thickness of 4 to 6 mm after demolding; placing the rectangular block on an automatic rolling device for rolling, first preliminarily adjusting the distance between the rollers to 4 to 5 mm, the rolling temperature to 30 to 40° C., and the rolling rate to 0.2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and repeatedly rolled, and this step is repeated 4 to 5 times to obtain a rectangular block with a thickness of 4 to 5 mm;

[0069] (4) The distance between the rollers is adjusted to 1.2 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth I with a thickness of 1.2 mm; the distance between the rollers is adjusted to 0.8 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth II with a thickness of 0.8 mm.

[0070] (5) The metal cloth I and the metal cloth II obtained in step (4) are superimposed, the roller spacing is adjusted to 1.5 mm, and a gradient metal cloth is formed by rolling.

[0071] Example 4

[0072] A gradient metal cloth comprises metal cloth I and metal cloth II; wherein metal cloth I comprises mixed powder (by mass percentage, 40% WC powder and 60% NiCrBSi powder) and organic additives; metal cloth II comprises mixed powder (by mass percentage, 60% WC powder and 40% NiCrBSi powder) and organic additives. In both metal cloth I and metal cloth II, the mass ratio of mixed powder to organic additives is 30:1.

[0073] The method for preparing the metal coating comprises the following steps:

[0074] (1) Weighing WC powder and NiCrBSi alloy powder according to mass percentage, mixing them to obtain a mixed powder;

[0075] (2) adding the mixed powder obtained in step (1) and the organic additive in a mass ratio of 30:1 into a ball mill with a ball-to-material ratio of 5:1 and a rotation speed of 230 rpm, and running the mill in a forward-reverse alternating manner for 1 hour to obtain a uniform mixture;

[0076] (3) placing the uniform mixture obtained in step (2) in a rectangular mold frame for compaction, and obtaining a rectangular block with a thickness of 4 to 6 mm after demolding; placing the rectangular block on an automatic rolling device for rolling, first preliminarily adjusting the distance between the rollers to 4 to 5 mm, the rolling temperature to 30 to 40° C., and the rolling rate to 0.2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and repeatedly rolled, and this step is repeated 4 to 5 times to obtain a rectangular block with a thickness of 4 to 5 mm;

[0077] (4) The distance between the rollers is adjusted to 1.2 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth I with a thickness of 1.2 mm; the distance between the rollers is adjusted to 0.8 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth II with a thickness of 0.8 mm.

[0078] (5) The metal cloth I and the metal cloth II obtained in step (4) are superimposed, the roller spacing is adjusted to 1.5 mm, and a gradient metal cloth is formed by rolling.

[0079] Example 5

[0080] A gradient metal cloth comprises metal cloth I and metal cloth II; wherein metal cloth I comprises mixed powder (by mass percentage, 50% WC powder and 50% NiCrBSi powder) and organic additives; metal cloth II comprises mixed powder (by mass percentage, 50% WC powder and 50% NiCrBSi powder) and organic additives. In both metal cloth I and metal cloth II, the mass ratio of the mixed powder to the organic additive is 30:1.

[0081] The method for preparing the metal coating comprises the following steps:

[0082] (1) Weighing WC powder and NiCrBSi alloy powder according to mass percentage, mixing them to obtain a mixed powder;

[0083] (2) adding the mixed powder obtained in step (1) and the organic additive in a mass ratio of 30:1 into a ball mill with a ball-to-material ratio of 5:1 and a rotation speed of 230 rpm, and running the mill in a forward-reverse alternating manner for 1 hour to obtain a uniform mixture;

[0084] (3) placing the uniform mixture obtained in step (2) in a rectangular mold frame for compaction, and obtaining a rectangular block with a thickness of 4 to 6 mm after demolding; placing the rectangular block on an automatic rolling device for rolling, first preliminarily adjusting the distance between the rollers to 4 to 5 mm, the rolling temperature to 30 to 40° C., and the rolling rate to 0.2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and repeatedly rolled, and this step is repeated 4 to 5 times to obtain a rectangular block with a thickness of 4 to 5 mm;

[0085] (4) The distance between the rollers is adjusted to 1.2 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth I with a thickness of 1.2 mm; the distance between the rollers is adjusted to 0.8 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly. This step is repeated 4 to 5 times to obtain a metal cloth II with a thickness of 0.8 mm.

[0086] (5) The metal cloth I and the metal cloth II obtained in step (4) are superimposed, the roller spacing is adjusted to 1.5 mm, and a gradient metal cloth is formed by rolling.

[0087] The gradient metal cloth prepared in the above-mentioned Examples 1 to 5 is coated on the surface of the metal substrate, and a wear-resistant coating on the metal surface is prepared by vacuum brazing technology.

[0088] Example 6

[0089] The preparation method of the wear-resistant coating on the surface of 45 steel pipe is as follows:

[0090] (1) Prepare a DN50×10×50 45 steel pipe, polish the surface of the 45 steel pipe with sandpaper, put it into acetone for ultrasonic cleaning, blow dry, and evenly apply silicone epoxy resin AB glue on the surface of the 45 steel pipe; cut the gradient metal cloth prepared in Example 1 into a size of 50×160×1.5 mm, cover the surface of the 45 steel pipe with the cut gradient metal cloth, then cover the surface of the metal cloth with a high-temperature resistant ceramic fiber mat, and wrap and fasten it with a steel mesh;

[0091] (2) Place the prepared sample in a vertical position at a vacuum degree of 7.0×10 -3 Pa vacuum brazing furnace, the temperature was raised to 350°C at a rate of 10°C / min, kept warm for 30 min, then continued to be heated to 1050°C, kept warm for 20 min, and then cooled to 700°C at a rate of 5°C / min, cooled to room temperature with the furnace, and the sample was taken out.

[0092] Through observation, the surface coating of 45 steel pipe is uniform and flat, well formed, and forms a dense interface bonding. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0093] Example 7

[0094] The preparation method of the wear-resistant coating on the surface of 45 steel pipe is as follows:

[0095] (1) Prepare a DN50×10×50 45 steel pipe, polish the surface of the 45 steel pipe with sandpaper, put it into acetone for ultrasonic cleaning, blow dry, and evenly apply silicone epoxy resin AB glue on the surface of the 45 steel pipe; cut the gradient metal cloth prepared in Example 2 into a size of 50×160×1.5 mm, cover the surface of the 45 steel pipe with the cut gradient metal cloth, then cover the surface of the metal cloth with a high-temperature resistant ceramic fiber mat, and wrap and fasten it with a steel wire mesh;

[0096] (2) Place the prepared sample in a vertical position at a vacuum degree of 7.0×10 -3 Pa vacuum brazing furnace, the temperature was raised to 350°C at a rate of 10°C / min, kept warm for 30 min, then continued to be heated to 1080°C, kept warm for 15 min, and then cooled to 700°C at a rate of 5°C / min, cooled to room temperature with the furnace, and the sample was taken out.

[0097] Through observation, the surface coating of 45 steel pipe is uniform and flat, well formed, and forms a dense interface bonding. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0098] Example 8

[0099] The preparation method of the wear-resistant coating on the surface of 45 steel pipe is as follows:

[0100] (1) Prepare a DN50×10×50 45 steel pipe, polish the surface of the 45 steel pipe with sandpaper, put it into acetone for ultrasonic cleaning, blow dry, and evenly apply silicone epoxy resin AB glue on the surface of the 45 steel pipe; cut the gradient metal cloth prepared in Example 3 into a size of 50×160×1.5 mm, cover the surface of the 45 steel pipe with the cut gradient metal cloth, then cover the surface of the metal cloth with a high-temperature resistant ceramic fiber mat, and wrap and fasten it with a steel wire mesh;

[0101] (2) Place the prepared sample in a vacuum chamber with a vacuum degree of 7.0×10 -3 Pa vacuum brazing furnace, the temperature was raised to 350°C at a rate of 10°C / min, kept warm for 30 min, then continued to be heated to 1080°C, kept warm for 15 min, and then cooled to 700°C at a rate of 5°C / min, cooled to room temperature with the furnace, and the sample was taken out.

[0102] Through observation, the surface coating of 45 steel pipe is uniform and flat, well formed, and forms a dense interface bonding. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0103] Example 9

[0104] The preparation method of the wear-resistant coating on the surface of 45 steel pipe is as follows:

[0105] (1) Prepare a DN50×10×50 45 steel pipe, polish the surface of the 45 steel pipe with sandpaper, put it into acetone for ultrasonic cleaning, blow dry, and evenly apply silicone epoxy resin AB glue on the surface of the 45 steel pipe; cut the gradient metal cloth prepared in Example 4 into a size of 50×160×1.5 mm, cover the surface of the 45 steel pipe with the cut gradient metal cloth, then cover the surface of the metal cloth with a high-temperature resistant ceramic fiber mat, and wrap and fasten it with a steel mesh;

[0106] (2) Place the prepared sample in a vacuum chamber with a vacuum degree of 7.0×10 -3 Pa vacuum brazing furnace, the temperature was raised to 350°C at a rate of 10°C / min, kept warm for 30 min, then continued to be heated to 1080°C, kept warm for 15 min, and then cooled to 700°C at a rate of 5°C / min, cooled to room temperature with the furnace, and the sample was taken out.

[0107] Through observation, the surface coating of 45 steel pipe is uniform and flat, well formed, and forms a dense interface bonding. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0108] Example 10

[0109] The preparation method of the wear-resistant coating on the surface of 45 steel pipe is as follows:

[0110] (1) Prepare a DN50×10×50 45 steel pipe, polish the surface of the 45 steel pipe with sandpaper, put it into acetone for ultrasonic cleaning, blow dry, and evenly apply silicone epoxy resin AB glue on the surface of the 45 steel pipe; cut the gradient metal cloth prepared in Example 5 into a size of 50×160×1.5 mm, cover the surface of the 45 steel pipe with the cut gradient metal cloth, then cover the surface of the metal cloth with a high-temperature resistant ceramic fiber mat, and wrap and fasten it with a steel mesh;

[0111] (2) Place the prepared sample in a vacuum chamber with a vacuum degree of 7.0×10 -3 Pa vacuum brazing furnace, the temperature was raised to 350°C at a rate of 10°C / min, kept warm for 30 min, then continued to be heated to 1080°C, kept warm for 15 min, and then cooled to 700°C at a rate of 5°C / min, cooled to room temperature with the furnace, and the sample was taken out.

[0112] Through observation, the surface coating of 45 steel pipe is uniform and flat, well formed, and forms a dense interface bonding. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0113] Comparative Example 1

[0114] The technical scheme is the same as that of Example 1, except that the ratio of the mixed powder to the organic additive is changed to 5:1, and the other parts remain unchanged. The wear-resistant coating prepared is welded on the surface coating of 45 steel pipe according to the method in Example 6. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0115] Comparative Example 2

[0116] The technical scheme is the same as that of Example 1, except that the ratio of the mixed powder to the organic additive is changed to 10:1, and the other parts remain unchanged. The wear-resistant coating prepared is welded on the surface coating of 45 steel pipe according to the method in Example 6. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0117] Comparative Example 3

[0118] The technical scheme is the same as that of Example 1, except that the ratio of the mixed powder to the organic additive is changed to 20:1, and the other parts remain unchanged. The prepared wear-resistant coating is welded to the surface coating of 45 steel pipe according to the method in Example 6. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0119] Comparative Example 4

[0120] The technical scheme is the same as that of Example 1, except that the ratio of the mixed powder to the organic additive is changed to 40:1, and the other parts remain unchanged. The wear-resistant coating prepared is welded on the surface coating of 45 steel pipe according to the method in Example 6. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0121] Comparative Example 5

[0122] The technical scheme is the same as that of Example 1, except that the ratio of the mixed powder to the organic additive is changed to 50:1, and the other parts remain unchanged. The wear-resistant coating prepared is welded to the surface coating of 45 steel pipe according to the method in Example 6. The surface of the coating material is tested at multiple points, and the test results are shown in Table 1 below.

[0123] Table 1 Comparison of test results of surface coating on 45 steel welded in Examples 6-10 and Comparative Examples 1-5

[0124]

[0125] By comparing the data of each group in Table 1 above, it can be found that in Examples 6 to 9, the greater the NiCrBSi powder content in the metal cloth I, the higher the bonding strength between the coating and the substrate; and the greater the WC particle content in the metal cloth II, the greater the hardness of the coating.

[0126] Organic additives mainly play a bonding role, turning nickel-based powder and tungsten carbide powder into an organic whole, which helps to roll them into cloth. During the vacuum brazing process, organic additives evaporate completely at 350°C, do not participate in the metallurgical reaction between nickel-based tungsten carbide and the metal matrix, and will not be mixed in the metal coating, so they will not affect the hardness and shear strength of the coating. Organic additives mainly affect the molding of metal cloth, and then affect the macroscopic morphology of the coating. The amount of adhesive added affects the macroscopic morphology of the coating surface. Figure 1As shown, the ratio of the mixed powder to the organic additive is 5:1, 10:1, 20:1, 30:1, 40:1, 50:1 from left to right, and the proportion of the organic additive gradually decreases. When the content of the organic additive is 5:1, 10:1, and 20:1, the rolled metal cloth does not disperse, the metal cloth is hard, and the toughness is poor. During the vacuum brazing process, all the organic additives are volatilized, and the remaining nickel-based tungsten carbide powder content is small, and the prepared coating has obvious cracks and gullies. The higher the proportion of organic additives, the more obvious the degree of cracks and gullies. The coating with obvious defects is not enough for mechanical property testing, resulting in the lack of hardness and bonding strength data of experimental comparative examples 1 and 2. When the ratio is 30:1, the rolled metal cloth has beautiful shape, good toughness, and can be folded. The macroscopic morphology of the coating obtained in Example 6 is the best, with metallic luster, smooth surface, and dense molding. When the content of organic additives is 40:1 and 50:1, the rolled metal cloth has poor toughness and is easy to disperse. The low content of organic additives affects the forming of the metal cloth, and the poor forming of the metal cloth further affects the surface macroscopic morphology of the coating. The surface of the coating obtained in Comparative Examples 4 and 5 is rough. The mechanical test data of Comparative Examples 3 to 5 are good, but Comparative Example 3 has a small amount of cracks and gullies, and the surface of the coating of Comparative Examples 4 and 5 is rough. The wear-resistant coating has surface defects and poor practicality. Therefore, when the ratio of metal powder to organic additives is 30:1, the rolled metal cloth has beautiful forming and good toughness. The prepared coating has the best macroscopic morphology, metallic luster, smooth surface, dense forming, and practicality.

[0127] As the proportion of WC hard particles in the outer metal cloth II increases within a limited range, the hardness will gradually increase. A further increase in the WC content will lead to a decrease in the metallurgical bonding between it and the brazing material. Figures 2 to 6As shown in the figure, the supporting effect of the brazing material on it is weakened, and even some gaps between WC particles are not filled by liquid brazing material, forming pores in the coating, and the surface is prone to cracking. There is not enough liquid brazing material to wet the substrate surface, and the bonding strength between the coating and the metal substrate is low. Through the gradient metal cloth, the proportion of NiCrBSi in the inner metal cloth I increases, so that there is enough brazing material to wet the WC and metal substrate surfaces and fill the gaps between the WC particles. During the vacuum brazing process, the outer metal cloth II is mainly composed of WC, and the inner metal cloth I is mainly composed of NiCrBSi. During the vacuum brazing process, WC remains solid, and the metal cloth II as a whole moves downward in the NiCrBSi liquid phase of the metal cloth I. The combination of gradient metal cloth ensures that the surface of the coating has high hardness and high wear resistance, as well as high bonding strength. The best gradient metal cloth combination is that metal cloth I includes mixed powder (10% WC powder, 90% NiCrBSi powder) and organic additives; metal cloth II includes mixed powder (90% WC powder, 10% NiCrBSi powder) and organic additives. In metal cloth I and metal cloth II, the mass ratio of mixed powder to organic additive is 30:1. The surface coating test results are as follows: the surface Rockwell hardness is 87HRC and the bonding strength is 425MPa.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A wear-resistant coating with adjustable hardness and high bonding strength, characterized in that: The wear-resistant coating is obtained by stacking and rolling metal cloth I and metal cloth II into a gradient metal cloth, placing it on the surface of a 45 steel pipe and adopting a vacuum brazing process; wherein the metal cloth I and the metal cloth II are both prepared by powder mixing, ball milling and rolling processes, and the raw materials include WC powder, NiCrBSi powder and organic additives; wherein the hardness of the wear-resistant coating is regulated by adjusting the ratio of WC powder to NiCrBSi powder in the metal cloth, and the bonding strength between the wear-resistant coating and the substrate is improved.

2. The wear-resistant coating with adjustable hardness and high bonding strength according to claim 1, characterized in that: In terms of mass percentage, in the metal cloth I, WC powder: NiCrBSi powder = 10%: 90%~50%: 50%; in the metal cloth II, WC powder: NiCrBSi powder = 90%: 10%~50%: 50%; the mass ratio of the mixed powder composed of WC powder and NiCrBSi powder to the organic additive in metal cloth I and metal cloth II is 30:

1.

3. The wear-resistant coating with adjustable hardness and high bonding strength according to claim 2, characterized in that: Calculated by mass percentage, in the metal cloth I, WC powder: NiCrBSi powder = 10%: 90%; in the metal cloth II, WC powder: NiCrBSi powder = 90%: 10%.

4. The wear-resistant coating with adjustable hardness and high bonding strength according to claim 1, characterized in that: The organic additive consists of 2.4wt.% dispersant, 9.6wt.% binder, 4wt.% plasticizer and 84wt.% solvent; the dispersant is Hypermer KD-1; the binder is PVB; the plasticizer is PEG and glycerol; and the solvent is anhydrous ethanol and butanone.

5. The method for preparing the gradient metal cloth in the wear-resistant coating with adjustable hardness and high bonding strength as claimed in any one of claims 1 to 4, characterized in that: Here are the steps: (1) Weighing WC powder and NiCrBSi alloy powder according to mass percentage, mixing them to obtain a mixed powder; (2) The mixed powder obtained in step (1) and the organic additive are added into a ball mill at a mass ratio of 30:1, and after ball milling, a uniform mixture is obtained; (3) placing the uniform mixture obtained in step (2) into a mold, and after demolding, obtaining a rectangular block with a thickness of 4 to 6 mm; rolling the rectangular block, preliminarily adjusting the distance between the rollers to 4 to 5 mm, the rolling temperature to 30 to 40° C., the rolling rate to 0.2 m / min, the rectangular block passes through the rollers, is folded, and rotated 90°, and this step is repeated 4 to 5 times to obtain a rectangular block with a thickness of 4 to 5 mm; (4) The distance between the rollers is adjusted to 1.2 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly, and this step is repeated 4 to 5 times to obtain a metal cloth I with a thickness of 1.2 mm; the distance between the rollers is adjusted to 0.8 mm, the rolling rate is 2 m / min, the rectangular block passes through the rollers, is folded, rotated 90°, and rolled repeatedly, and this step is repeated 4 to 5 times to obtain a metal cloth II with a thickness of 0.8 mm; (5) The metal cloth I and metal cloth II obtained in step (4) are stacked, the roller spacing is adjusted to 1.5 mm, and a gradient metal cloth is formed by rolling.

6. The method for preparing the gradient metal cloth according to claim 5, characterized in that: In the step (2), the ball-to-material ratio of the ball mill is 5:1, the rotation speed is 230 rpm, and the time is 1 hour; the ball milling method is forward rotation-reverse rotation alternating operation.

7. The method for preparing the gradient metal cloth according to claim 5, characterized in that: In the step (5), the metal cloth is superimposed and rolled in such a manner that the metal cloth II is on the upper side as a layer away from the substrate, and the metal cloth I is on the lower side as a layer close to the substrate.

8. Application of the gradient metal cloth in the wear-resistant coating with adjustable hardness and high bonding strength as described in any one of claims 1 to 4 in metal surface processing, the method being: preparing the wear-resistant coating on the surface of the metal substrate by vacuum brazing.

9. The use according to claim 8, characterized in that: Here are the steps: (1) Apply silicone epoxy resin AB glue evenly on the surface of DN50×10×50 45 steel pipe; cut the gradient metal cloth into a size of 50×160×1.5m, wrap the cut gradient metal cloth on the surface of 45 steel pipe, then cover the surface of the metal cloth with high temperature resistant ceramic fiber mat, and wrap and fasten it with steel wire mesh; (2) Place the prepared sample upright in a vacuum brazing furnace, heat it to 350°C at a heating rate of 10°C / min, keep it warm for 30 minutes, then continue to heat it to 1050°C, keep it warm for 20 minutes, and then cool it to 700°C at a rate of 5°C / min. Cool it to room temperature with the furnace, take out the sample, and the surface processing of the 45 steel pipe is completed.

Citation Information

Patent Citations

  • Penetration brazing preparation method of high-content wolfram carbide gradient wear-resisting coating

    CN102965663A

  • Preparation technology of abrasion-resistant stainless steel alloy coating

    CN109692957A

  • Preparation and welding method of cladding coating and special device thereof

    CN117943648A